2019
DOI: 10.1103/physrevlett.123.235101
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance of the Front Region of Magnetic Reconnection Outflow Jets due to the Lower-Hybrid Drift Instability

Abstract: A 3D fully kinetic simulation shows that the lower-hybrid drift instability disturbs the front of magnetic reconnection outflow jets and additionally causes energy dissipation. The result is very consistent with a disturbance observed at the dipolarization front (DF) in Earth's magnetotail by the Magnetospheric Multiscale (MMS) mission. A fully kinetic dispersion relation solver, validated by the MMS observations, further predicts that the disturbance of the reconnection jet front could occur over different pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 31 publications
1
17
1
Order By: Relevance
“…The location and generation of the LHDI discussed here differs from what is expected in eigenmode studies (Daughton, 1999(Daughton, , 2003 and other simulations (Divin et al, 2015;Lapenta et al, 2018;Le et al, 2017;Nakamura et al, 2019;Price et al, 2016;Roytershteyn et al, 2012). Here the perpendicular current and density gradient associated with the generation of the LHDI are found in the electron outflow rather than the edge of the current sheet, the separatrix surface or where the jet interacts with the ambient downstream plasma, and the electron flow driving the instability is in the outflow direction rather than being part of the initial equilibrium causing the direction of propagation of the LHDI to be mostly in the x direction.…”
Section: Resultscontrasting
confidence: 89%
See 1 more Smart Citation
“…The location and generation of the LHDI discussed here differs from what is expected in eigenmode studies (Daughton, 1999(Daughton, , 2003 and other simulations (Divin et al, 2015;Lapenta et al, 2018;Le et al, 2017;Nakamura et al, 2019;Price et al, 2016;Roytershteyn et al, 2012). Here the perpendicular current and density gradient associated with the generation of the LHDI are found in the electron outflow rather than the edge of the current sheet, the separatrix surface or where the jet interacts with the ambient downstream plasma, and the electron flow driving the instability is in the outflow direction rather than being part of the initial equilibrium causing the direction of propagation of the LHDI to be mostly in the x direction.…”
Section: Resultscontrasting
confidence: 89%
“…First, we distinguish the MMS‐discovered LHDI from previous simulation and observational studies of the LHDI related to reconnection. Typically, the short‐wavelength LHDI with k ⊥ ρ e ∼ 1 is observed at the upstream edge of the current sheet (Carter et al, 2001), the downstream jet front where the outflow interacts with the ambient plasma (Divin et al, 2015; Lapenta et al, 2018; Nakamura et al, 2019) and is stabilized at the center of the current layer (Carter et al, 2002; Daughton, 2003), while only the longer wavelength electromagnetic LHDI with kρeρi1 is found at the centre of the current sheet. The LHDI has been shown to cause electromagnetic fluctuations in simulations (Daughton, 2003) and laboratory experiments (Ji et al, 2004), which may contribute to anomalous resistivity and viscosity (Le et al, 2017; Price et al, 2016; Roytershteyn et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al., 2010). Specifically, electrons can be efficiently accelerated by adiabatic processes, such as Fermi and betatron mechanisms, respectively (H. S. Fu et al., 2011, 2019; C. M. Liu, Fu, Xu, Cao, et al., 2017; C. M. Liu, Fu, Xu, Wang, et al., 2017; Lu, Angelopoulos, et al., 2016; Lu, Artemyev, et al., 2016; Q. Pan et al., 2012; Vaivads et al., 2011; M. Y. Wu et al., 2013; Xu et al., 2018); or nonadiabatic processes, for example, wave‐particle interaction (Huang et al., 2012; Hwang et al., 2014; Khotyaintsev et al., 2011; T. K. M. Nakamura et al., 2019; H. S. Fu, Zhao, et al., 2020). It has been suggested that the intense current and electric fields can result in strong energy conversion at the DFs (Angelopoulos et al., 2013; Huang, Fu, Yuan, et al., 2015; Khotyaintsev et al., 2017; Lapenta et al., 2014; C. M. Liu, Fu, Vaivads, et al., 2018; Yang et al., 2017; Z. H. Yao et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…M. Liu, Fu, Xu, Khotyaintsev, et al, 2018;C. M. Liu, Fu, Vaivads, 2018b;Nakamura et al, 2019;Zhou et al, 2009), (b) structureless whistler waves inside the FPR/DFB (Breuillard et al, 2016;Deng et al, 2010;Huang et al, 2012Huang et al, , 2016Hwang et al, 2014;Khotyaintsev et al, 2011;Le Contel et al, 2009;Li et al, 2015;Viberg et al, 2014;Zhang et al, 2018), (c) discrete chorus waves inside the FPR (Fu et al, 2014), (d) electron cyclotron harmonic waves inside the FPR (Fu et al, 2014;Zhang & Angelopoulos, 2014;Zhou et al, 2009), (e) electromagnetic ion cyclotron waves inside the FPR (Huang et al, 2015), (f) magnetosonic waves inside the FPR (Fu, Zhao, et al, 2020), (g) electrostatic solitary waves inside the FPR (Deng et al, 2010;Fu et al, 2020c;, and (h) the broadband high-frequency waves at the DF boundary (Yang et al, 2017). Among these waves, lower hybrid drift waves and whistler waves are the two most frequent ones and have been extensively investigated in previous studies.…”
Section: Chen Et Almentioning
confidence: 99%
“…Since these two types of waves have different generation mechanisms, they prefer to appear in different regions. Specifically, the lower hybrid drift waves are excited by density and magnetic gradients (Divin et al., 2015a; C. M. Liu, Fu, Xu, Khotyaintsev, et al., 2018; Nakamura et al., 2019), so they primarily appear at the DF boundary, where the density and magnetic gradients are large; the whistler waves are excited by electron perpendicular anisotropies (or termed pancake distributions) (e.g., Le Contel et al., 2009; Li et al., 2015; Khotyaintsev et al., 2011), and thus they primarily appear inside the FPR, where the pancake distribution of suprathermal electrons are very common (Fu, Cao, Zong, et al., 2012). A textbook example of an event with lower hybrid drift waves at the DF boundary and whistler waves inside the FPR is reported by Khotyaintsev et al.…”
Section: Introductionmentioning
confidence: 99%